ANALYSIS OF THE EFFECTS OF WORK DISCIPLINE AND INDIVIDUAL CHARACTERISTICS ON EMPLOYEE PERFORMANCE - Nainggolan, Nana Triapnita; Lie, Darwin; Nainggolan, Lora Ekana (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Komputer Indonesia, 2021)
In order to improve the performance of government agencies towards professionalism and support the creation of good public services, human resources who have work discipline and good individual character are needed. The purpose of this study was to determine the contribution given by work discipline and individual characteristics to employee performance. This research method uses a quantitative approach using qualitative and quantitative descriptive analysis. The data collection used a questionnaire and the sampling technique used a saturated sample with a total sample of 42 employees. From the research results, it can be concluded that: work discipline and individual characteristics, and employee performance are good. There is a positive influence between work discipline and individual characteristics on employee performance. Work discipline and individual characteristics have a strong relationship with employee performance. Hypothesis test results show that there is a positive and significant influence between work discipline and individual characteristics on employee performance.